2012
DOI: 10.1074/jbc.m112.371294
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Prenylated RhoA Interaction with Its Chaperone, RhoGDI

Abstract: Background: RhoGDI is a key regulator and a chaperon of Rho GTPases. Results: RhoGDI strongly discriminates between GDP-and GTP-bound forms of prenylated RhoA, although both complexes are of high affinity. Conclusion: We provide direct evidence for the existence of two populations of the RhoGDI⅐RhoA complexes in the cell, characterized by different lifetimes. Significance: The obtained data allows us to formulate the model for membrane delivery and extraction of Rho GTPases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 60 publications
4
72
1
Order By: Relevance
“…Prenylation is critical for the functioning of Rho proteins, as it enables them to reversibly associate with intracellular membranes [2] and promote binding to their key regulators, such as GDP exchange factors (GEFs) [3] and Rho GTPase-activating proteins (GAPs) [3,4]. An additional level of Rho regulation is brought about by the Rho GDP dissociation inhibitors (RhoGDIs) [5]. Three human RhoGDIs have been identified with the first isoform, RhoGDI-1 (here, RhoGDI), being most ubiquitously expressed and associating with most of the Rho proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Prenylation is critical for the functioning of Rho proteins, as it enables them to reversibly associate with intracellular membranes [2] and promote binding to their key regulators, such as GDP exchange factors (GEFs) [3] and Rho GTPase-activating proteins (GAPs) [3,4]. An additional level of Rho regulation is brought about by the Rho GDP dissociation inhibitors (RhoGDIs) [5]. Three human RhoGDIs have been identified with the first isoform, RhoGDI-1 (here, RhoGDI), being most ubiquitously expressed and associating with most of the Rho proteins.…”
Section: Introductionmentioning
confidence: 99%
“…RhoGDIs undergo a high affinity interaction with the Rho proteins using an N-terminal regulatory arm contacting the switch regions and a C-terminal domain binding the isoprenyl group (Tnimov et al 2012). In contrast to the large number of RhoGEFs and RhoGAPs, there are only three known RhoGDIs in human (DerMardirossian and Bokoch 2005).…”
Section: Guanine Nucleotide Dissociation Inhibitorsmentioning
confidence: 98%
“…Importantly, in vivo or in vitro geranylgeranylated RhoA (RhoA-G) was prone to aggregation at micromolar concentrations, and the reported picomolar affinities of RhoA-G toward RhoGDI␣ are above the detection limit of ITC (data not shown) (14).…”
Section: Rhogdi␣ Is Endogenously Lysine Acetylated In Humanmentioning
confidence: 99%
“…The crystal structures of full-length RhoGDI␣ alone and in complex with RhoA, Cdc42, and Rac1 have been solved by NMR and by x-ray crystallography (11)(12)(13)(14). These studies revealed a modular structure of RhoGDI␣, a C-terminal immunoglobulin (Ig) domain forming a hydrophobic pocket accommodating the prenyl group of the RhoGNBPs and an N-terminal intrinsically unfolded domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation